Spectrophotometric Determination of Nickel and Palladium After Separation by Adsorption of Its Cyclohexylthioglycolate Complex on Microcrystalline Naphthalene - Gupta, Usha; Jeet, Varinder; Rao, A.L.J. (Asian Journal of Chemistry, 2010)
A new spectrophotometric method for the trace determination of nickel and palladium after, adsorption of its cyclohexylthioglycolate (CyHTG) complex on to microcrystalline naphthalene has been developed. The interference of various ions have been studied and the method has been applied to the determination of nickel and palladium in certain standard alloys and synthetic mixtures respectively.